Decreased Rhamnose Metabolic Flux Improved Production of Target Proteins and Cell Flocculation in Pichia pastoris - Yan, Chengliang; Xu, Xinxin; Zhang, Xue; Zhang, Yuwei; Zhang, Yuhong; Zhang, Zhifang; Zhang, Wei; Liu, Bo (Frontiers in Microbiology, 2018)
Previously, several genes, including LRA1-LRA4 and LRAR, involved in rhamnose utilization pathway were discovered in Pichia pastoris GS115; among them, LRA3 and LRA4 were considered as key rate-determining step enzymes. A P. pastoris expression platform based on the strong rhamnose-inducible promoter PLRA3 did not meet the demands of industrial application due to poor production of recombinant proteins. To enhance recombinant protein production of this expression platform, a genetically engineered strain, P. pastoris GS115m, with decreased rhamnose metabolic flux was developed from P. pastoris GS115 by replacement of the rhamnose-inducible promoter PLRA4 with another much weaker rhamnose-inducible promoter, PLRA2. Grown in MRH and YPR media using rhamnose as the main carbon source, the engineered strain showed decreased growth rate and maximal biomass compared with the parental strain. More importantly, grown in rhamnose-containing MRH and YPR media, the recombinant engineered strain harboring a β-galactosidase gene lacB, whose expression was regulated by rhamnose-inducible PLRA3, yielded substantial increases, of 2.5-fold and 1.5-fold, respectively, in target protein production over the parental strain. Additionally, grown in MRH and YPR media, the engineered strain had remarkable cell flocculation and rapid sedimentation with the increasing of cell density, providing an effective and convenient separation of the fermentation supernatant from strain cells. The engineered strain is a promising expression host for industrial production of target proteins due to its advantages over the parental strain as follows: (i) improved production of recombinant proteins; and (ii) remarkable cell flocculation and rapid sedimentation.